2001
DOI: 10.1677/joe.0.1690023
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, mitosis orientation and morphogenetic changes in the uterus of mice following chronic treatment with both estrogen and glucocorticoid hormones

Abstract: Glucocorticoids have been known to be involved in the regulation of some aspects of estrogen action on the uterus. However, the effect of glucocorticoids on changes in uterine morphogenes produced by chronic estrogen exposure is not known. Therefore, the aim of this work was to examine the role of glucocorticoids on proliferative and morphogenetic uterine reactions induced by continuous estrogen treatment. Ovariectomized mice received subcutaneous injections of estradiol dipropionate in olive oil (2 µg per 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 31 publications
5
35
0
2
Order By: Relevance
“…In our previous experiments, treatments sometimes had an effect on proliferation but had no action on morphogenetic changes in the uterus, and vice versa (Gunin et al 2001(Gunin et al , 2004a. The present results show that histone deacetylase blockers affect both proliferation and morphogenetic alterations.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…In our previous experiments, treatments sometimes had an effect on proliferation but had no action on morphogenetic changes in the uterus, and vice versa (Gunin et al 2001(Gunin et al , 2004a. The present results show that histone deacetylase blockers affect both proliferation and morphogenetic alterations.…”
Section: Discussionsupporting
confidence: 65%
“…Our previous observations clearly showed that treatment with estradiol for 30 days was quite enough to produce expressed estrogen-dependent changes in uterine morphology and to induce hyperplastic changes in the uterus (Gunin et al 2001(Gunin et al , 2002(Gunin et al , 2004a. This estradiol dose and treatment regime produced estradiol levels in the blood that were close to the normal physiologic values (Gunin et al 2004a).…”
Section: Treatmentsmentioning
confidence: 74%
See 3 more Smart Citations